The Case Study of Capital Structure in Affecting Return on Equity (ROE) Among Chinese Companies - Wee Win Yeoh (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2024)
The case study for the capital structure research had been crucial to address the financial performance for the business. In the recent trend of business, the strategic development of the business growth had been dependent on the capital structure funding where the ratio between the debt and equity often become the pillar to determine the financial performance for the business. This triggered the study to develop the quantitative method research to explore the relationship of debt equity ratio representing the capital structure funding for business against the return on equity (ROE) representing the financial performance of the business. The target study will be based on the public listed companies in China mainly from Shanghai Stock Exchange (SSE) and Shenzhen Stock Exchange (SZSE). The results and findings from the quantitative study had found the significant positive relationship being exist between the debt equity ratio and ROE which aligned with the initial assessment from the literature review. This had been crucial contribution for the investors to understand the potential earning derived from the ROE inducing the understanding where the higher debt funding will encourage better return on the equity investment which will become more important consideration among the investors.